A chirp-based wideband spread spectrum modulation technique for WLAN applications - Gugler, Wolfgang; Springer, Andreas; Weigel, Robert (IEEE Sixth International Symposium on Spread Spectrum Techniques and Applications, 2000)
A high data-rate wideband chirp spread spectrum system for indoor communications is presented. We propose the use of chirp signals with the well known pulse compression technique to make the system extremely robust and therefore suitable for applications in an industrial environment. By using π/4-DQPSK modulation of the chirp signals, overlapping chirp signals, and optimized chirp signal design we achieve data rates up to 70 Mbps. There is no need for sophisticated digital signal processing due to the use of surface acoustic wave (SAW) filters for the generation and filtering of the chirp signals. System imperfections like production tolerances, temperature drift, nonlinearities, and others are shown to be either negligible or can be easily handled. Simulation results reveal that the limiting factor for the data rate is intersymbol interference caused by multipath propagation
elib2cris::1512001600,gugler2000a
Keywords: wideband; WLAN